Evaluation of the antiviral activities of Bacharis dracunculifolia and quercetin on Equid herpesvirus 1 in a murine model. (October 2018) - Ferreira, Caroline Gracielle Torres; Campos, Mateus Gandra; Felix, Daniele Mendes; Santos, Marcus Rebouças; Carvalho, Otávio Valério de; Diaz, Marisa Alves Nogueira; Fietto, Juliana Lopes Rangel; Bressan, Gustavo Costa; Silva-Júnior, Abelardo; Almeida, Márcia Rogéria de
Abstract: Equid herpesvirus 1 (EHV-1) is a pathogen of high economic importance in equine breeding operations around the world. EHV-1 infection causes respiratory, neurologic and reproductive disease. The absence of an efficient therapy has caught the attention of the scientific community and the therapeutic activities of natural products with its antivirals effects might be effective for the disease's treatment. Herein it was evaluated the prophylactic and therapeutic potential of quercetin and ethanolic extracts of Bacharis dracunculifolia formulations compared to Penciclovir® in an in vivo EHV-1 infection model. Six to seven-week-old female C57BL/6 mice were randomly organized into fifteen groups with six animals each. Ex-1 represents the treatment post-challenge groups to assess morbidity, mortality and weight variation. Ex-2 represents the animals that received treatment for 5 days post-challenge for lesion evaluation. In Ex-3 animals were treated prior to viral challenge to assess morbidity, mortality and weight variation. All mice in the treatment groups were challenged by intranasal inoculation of 3.0 × 10 5 TCID50 EHV-1. The quercetin and B. dracunculifolia treatment decreased morbimortality in post-challenge treatment (Ex-1) and EHV-1 related lesions (Ex-2). Treatment prior to viral challenge (Ex-3) did not show any significant results. Based on the results of the present study, both tested formulations are promising antiviral agents for the treatment of EHV-1 infection. Highlights: We used a murine model to study the therapeutic action of two new antiviral candidates against EHV1. Quercetin and extract of B. dracunculifolia attenuated clinical signs of the animals infected in the post-treatment. Quercetin and extract of B. dracunculifolia decreased lesions in mice challenged with EHV-1.